Do Financial Performance and Market Value Matter? Evidence on Stock Returns in the Pharmaceutical Industry - Muhammad Rofi'i; Alyta Shabrina Zusryn; Nurul Huda; Ariel Nian Gani; Muhammad Faisal; Ahmad Syarif (UPY Business and Management Journal (UMBJ), 2026)
Purpose: This study investigates whether the effects of market value, profitability, leverage, and liquidity on stock returns differ across economic conditions in the Indonesian pharmaceutical industry during the pre-pandemic (2018–2019), pandemic (2020–2022), and post-pandemic recovery (2023–2024) periods. Methodology: Using a quantitative approach, panel data regression was applied to seven pharmaceutical companies listed on the Indonesia Stock Exchange. Separate estimations were conducted for each phase to capture shifts in investor behavior over time. Findings: The results show that the influence of financial fundamentals on stock returns varies across economic conditions. Market value positively affects stock returns only in the pre-pandemic period. Profitability remains a positive and significant determinant throughout all periods, indicating investors’ consistent preference for firms with strong operating performance. Leverage changes from a negative factor before the pandemic to a positive factor during and after the pandemic, suggesting that debt is viewed as a strategic resource supporting growth. Liquidity is insignificant before the pandemic but becomes positively associated with stock returns during the pandemic and recovery periods, highlighting the importance of financial flexibility under uncertainty. Implications: Managers should prioritize sustainable profitability, effective debt utilization, and liquidity management to strengthen investor confidence. Investors should evaluate financial ratios according to prevailing economic conditions, as the relevance of financial indicators changes over time. Originality: This study contributes to the literature by demonstrating that the impact of financial fundamentals on stock returns is condition-dependent rather than constant, reflecting shifts in investor valuation behavior across different economic environments.